PATOLOGI BIROKRASI DAN DAMPAKNYA TERHADAP KUALITAS PELAYANAN PUBLIK DI KELURAHAN LAJONGA KABUPATEN SIDENRENG RAPPANG - Erna Muhamamad; Ahmad Mustanir; Irwan Irwan (LPPM Universitas Abdurrab, 2025)
This research is motivated by the persistence of bureaucratic pathology at the village administration level, which affects the quality of public services. The purpose of this study is to identify the forms of bureaucratic pathology occurring in Lajonga Village, Panca Lautang District, Sidenreng Rappang Regency, and to analyze their causal factors. This study applies a qualitative method with a descriptive approach, employing data collection techniques such as observation, in-depth interviews, and documentation. The findings reveal that bureaucratic pathology in Lajonga Village is reflected in the weak morality of officials, unclear working regulations, and recruitment and promotion practices that are not competency-based. The main causal factors include low integrity of officials, lack of supervision, and a work culture dominated by personal interests. These findings highlight the urgency of implementing good governance principles through strengthening integrity, enforcing discipline, and promoting a merit-based recruitment system to improve the quality of public services at the village administration level. Keywords: Patologi Birokrasi, Pelayanan Publik, Good Governance, Kelurahan Lajonga